(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
In India, the legal system has robust provisions to protect women from violence and abuse, reflecting the societal need to address gender-based injustices. However, the misuse of these laws against men has emerged as a significant concern, affecting the integrity of legal protections and the lives of innocent individuals. Legal provisions like Section 498A of the Indian Penal Code, designed to combat dowry harassment, and laws against sexual harassment and rape, are sometimes exploited to falsely accuse men for personal gain, revenge, or coercion. Such misuse leads to severe repercussions, including mental trauma, financial strain, social ostracism, and damage to reputation. The misuse of these laws also burdens the judicial system with false cases, diverting resources from genuine victims who need assistance. The societal stigma attached to men defending themselves against such allegations exacerbates their plight, often leaving them without adequate support. To address this issue, there is a growing call for legal reforms to ensure that laws intended to protect do not become tools for exploitation. Balanced legal frameworks, gender-neutral provisions, and stringent penalties for false accusations are necessary to safeguard the rights of all individuals and maintain the credibility of legal protections in India.